Impact of COVID‐19 on Otolaryngology Literature. (15th October 2021) - Chillakuru, Yeshwant R.; Gerhard, Eleanor F.; Shim, Timothy; Selesnick, Samuel H.; Lustig, Lawrence R.; Krouse, John H.; Hanna, Ehab Y.; Smith, Timothy L.; Fisher, Edward W.; Kerschner, Joseph E.; Monfared, Ashkan
Abstract : Objectives/Hypothesis: To understand the effect of the COVID‐19 pandemic on the volume, quality, and impact of otolaryngology publications. Study Design: Retrospective analysis. Methods: Fifteen of the top peer‐reviewed otolaryngology journals were queried on PubMed for COVID and non‐COVID‐related articles from April 1, 2020 to March 31, 2021 (pandemic period) and pre‐COVID articles from the year prior. Information on total number of submissions and rate of acceptance were collected from seven top‐ranked journals. Results: Our PubMed query returned 759 COVID articles, 4, 885 non‐COVID articles, and 4, 200 pre‐COVID articles, corresponding to a 34% increase in otolaryngology publications during the pandemic period. Meta‐analysis/reviews and miscellaneous publication types made up a larger portion of COVID publications than that of non‐COVID and pre‐COVID publications. Compared to pre‐COVID articles, citations per article 120 days after publication and Altmetric Attention Score were higher in both COVID articles (citations/article: 2.75 ± 0.45, P  < .001; Altmetric Attention Score: 2.05 ± 0.60, P  = .001) and non‐COVID articles (citations/article: 0.03 ± 0.01, P  = .002; Altmetric Attention Score: 0.67 ± 0.28, P  = .016). COVID manuscripts were associated with a 1.65 times higher acceptance rate compared to non‐COVID articles ( P  < .001). Conclusions: COVID‐19 was associated with an increase in volume, citations, and attention for both COVID and non‐COVID articles compared to pre‐COVID articles. However, COVID articles were associated with lower evidence levels than non‐COVID and pre‐COVID articles. Level of Evidence: 3 Laryngoscope, 132:1364–1373, 2022